Unusual deep vein thrombosis sites: magnetic resonance venography in patients with negative compression ultrasound and symptomatic pulmonary embolism. (February 2014) - Gary, T; Steidl, K; Belaj, K; Hafner, F; Froehlich, H; Deutschmann, H; Pilger, E; Brodmann, M
Objectives: To evaluate the clinical characteristics of patients with pulmonary embolism (PE), negative compression ultrasound (CUS) of the lower limbs and detection of unusual deep vein thrombosis (DVT) sites by means of magnetic resonance (MR) venography. Methods: A retrospective data analysis of PE patients hospitalized at our institution from April 2009 to 2011. Results: From April 2009 to 2011, a total of 762 PE patients were treated at our institution. In 169 of these patients CUS for DVT was negative. In these patients MR venography was performed for further evaluation. We found venous thrombosis at unusual sites in 12 of these patients. Due to free floating thrombus masses and fear of life-threatening PE progression we inserted an inferior vena cava filter in three of these 12 patients. The leading venous thromboembolism risk factor in our patients was immobilization (5 patients, 41.7%). Conclusions: We conclude that especially in patients with PE and negative CUS of the lower limbs a thrombosis of the pelvic veins should be considered in case of symptoms for venous thrombosis in this area. Further diagnostic work-up with MR venography should be scheduled in these patients especially in patients with risk factor immobilization as therapeutic consequences might occur.